2010
DOI: 10.2223/jped.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise during pregnancy and protein malnutrition during pregnancy and lactation on the development and growth of the offspring’s femur

Abstract: Objective: To evaluate the effects of physical training of mother rats during pregnancy associated with a low-protein diet offered during pregnancy and lactation on the development and growth of the femur of their offspring.Methods: Forty 90-day old male Wistar rats were divided into four groups: pups of sedentary nourished mothers, pups of sedentary malnourished mothers, pups of trained nourished mothers, and pups of trained malnourished mothers; all groups included 10 rats. Physical training on a treadmill f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(21 reference statements)
0
6
0
3
Order By: Relevance
“…The functional redistribution of muscle protein is necessary to supply the nitrogen required for essential functions during the early stages of life, such as blood cell formation, tissue protein synthesis, and immune function. Recent studies have shown that administration of low‐protein diets to rats during pregnancy can cause a reduction in offspring bone size . These findings may explain the reduction in soleus muscle length that was observed in RG animals.…”
Section: Discussionmentioning
confidence: 98%
“…The functional redistribution of muscle protein is necessary to supply the nitrogen required for essential functions during the early stages of life, such as blood cell formation, tissue protein synthesis, and immune function. Recent studies have shown that administration of low‐protein diets to rats during pregnancy can cause a reduction in offspring bone size . These findings may explain the reduction in soleus muscle length that was observed in RG animals.…”
Section: Discussionmentioning
confidence: 98%
“…The first two look at a similar problem from two different angles and arrive at similar conclusions. Monteiro et al 31 evaluated the effects of physical training of mother Wistar rats during pregnancy associated with a low-protein diet offered during pregnancy and lactation on the development and growth of the femur of their offspring. Pups were divided into offspring of sedentary nourished or malnourished mothers, pups of trained nourished or malnourished mothers.…”
Section: Resultsmentioning
confidence: 99%
“…They conclude that swimming helped the weight of the femur in the saline group but did not alter it between sedentary vs. exercised glutamine rats. We have already reviewed this paper by Monteiro et al 31 who evaluated the effects of physical training of mother Wistar rats during pregnancy associated with a low-protein diet offered during pregnancy and lactation on the development and growth of the femur of their offspring and found thatmild physical training on the treadmill during pregnancy did not interfere with bone development and growth of the offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, in rodents, varying effects of maternal exercise have been observed. Maternal treadmill running has been linked to smaller litters in some (Treadway et al 1986) though not all (Monteiro et al 2010) studies, but has not been associated with fetal or offspring body mass or length (Treadway et al 1986; Monteiro et al 2010). Also, maternal swimming has been associated with offspring having lower birth weight in one (Pinto & Shetty, 1995) but not all studies (Treadway & Lederman, 1986).…”
Section: Introductionmentioning
confidence: 99%